Characteristics of a New Device for Intubation Through a Laryngeal Mask Airway Over a Flexible Endoscope - Vivian VH (Dove Medical Press, 2021)
Vernon H Vivian,1 Tyson L Pardon,2 Samuel Vivian,3 André Van Zundert4,5 1Department of Anaesthesiology, Gympie General Hospital, Sunshine Coast, QLD, Australia; 2Emergency Department, Sunshine Cost Health Services, Sunshine Coast, QLD, Australia; 3Prehospital EMS, Queensland Ambulance Services, Brisbane, QLD, Australia; 4Department of Anesthesiology, Royal Brisbane & Women’s Hospital, Brisbane, Australia; 5The University of Queensland, Brisbane, QLD, AustraliaCorrespondence: Vernon H Vivian Email vjcsviv@hotmail.comAbstract: The laryngeal mask airway (LMA) is widely used for airway management in the emergency and elective treatment of patients in both the in-hospital and prehospital setting. The rate of prehospital use is increasing. The LMA is a vital link in the vortex approach to managing a difficult airway. Clinicians will be increasingly faced with the dilemma of managing the patient who has an LMA in place, but still requires the airway secured by an endotracheal tube (ETT). Flexible endoscopic intubation through an LMA is a simpler procedure than awake flexible endoscopic intubation. Furthermore, intubating flexible endoscopes are increasingly available and affordable (now single use) making its use out of the domains of the operating theater and intensive care unit feasible. The authors aim to inform clinicians about the indications, physical characteristics, and insertion/removal techniques related to a new device, the Rescue™ ETT (Genesis Airway Innovations®, Sunshine Coast, Australia), designed specifically for intubation through an LMA over a flexible endoscope and compare them to current devices used for this purpose.Keywords: laryngeal mask airway, intubation, fiberoptic, emergency, airway, scope, vortex